Prenatal exposure to methadone or buprenorphine impairs cognitive performance in young adult rats. (1st July 2020) - Kongstorp, Mette; Bogen, Inger Lise; Stiris, Tom; Andersen, Jannike Mørch
Highlights: Concerns have been raised about how OMT during pregnancy may affect the offspring. Prenatal methadone or buprenorphine exposure impaired cognitive functioning in rats. The cognitive deficits are not due to abstinences or poor maternal caregiving. Abstract: Background: Concerns have been raised about the use of opioid maintenance treatment (OMT) during pregnancy and negative effects for the offspring. While neonatal outcomes and short-term effects are relatively well described, studies examining long-term effects in adolescents and adults are absent. The aim of the present study was to examine effects on learning and memory in young adult rats prenatally exposed to methadone or buprenorphine. Methods: Female rats were implanted with a 28-day osmotic minipump delivering methadone (10 mg/kg/day), buprenorphine (1 mg/kg/day) or vehicle 5 days prior to mating. To examine possible effects on cognitive functioning, young adult offspring were included in three different behavioral tests that examine recognition memory, nonspatial, and spatial learning and memory. In addition, offspring growth and maternal behavior after birh were investigated. Results: Prenatal exposure to methadone or buprenorphine caused impaired recognition memory and nonspatial reference learning and memory in young adult rats compared with the vehicle-treated group. Methadone-exposed offspring, but not the buprenorphine-exposed, also showed reduced long-term spatial memory. We did not observe any changes in maternal behavior or offspring growth after prenatal exposure to methadone or buprenorphine, suggesting that the impaired cognitive functioning is due to the opioid exposure rather than reduced maternal caregiving. Conclusion: The present findings of long-term cognitive impairments in methadone- and buprenorphine-exposed offspring points to a negative impact of OMT on neurobiological development.